Validation of the in vivo assessment of pyruvate dehydrogenase activity using hyperpolarised 13C MRS - Atherton, Helen J.; Schroeder, Marie A.; Dodd, Michael S.; Heather, Lisa C.; Carter, Emma E.; Cochlin, Lowri E.; Nagel, Simon; Sibson, Nicola R.; Radda, George K.; Clarke, Kieran; Tyler, Damian J. (NMR in biomedicine, 2011)
Many diseases of the heart are characterised by changes in substrate utilisation, which is regulated in part by the activity of the enzyme pyruvate dehydrogenase (PDH). Consequently, there is much interest in the in vivo evaluation of PDH activity in a range of physiological and pathological states to obtain information on the metabolic mechanisms of cardiac diseases. Hyperpolarised [1-13C]pyruvate, detected using MRS, is a novel technique for the noninvasive evaluation of PDH flux. PDH flux has been assumed to directly reflect in vivo PDH activity, although to date this assumption remains unproven. Control animals and animals undergoing interventions known to modulate PDH activity, namely high fat feeding and dichloroacetate infusion, were used to investigate the relationship between in vivo hyperpolarised MRS measurements of PDH flux and ex vivo measurements of PDH enzyme activity (PDHa). Further, the plasma concentrations of pyruvate and other important metabolites were evaluated following pyruvate infusion to assess the metabolic consequences of pyruvate infusion during hyperpolarised MRS experiments. Hyperpolarised MRS measurements of PDH flux correlated significantly with ex vivo measurements of PDHa, confirming that PDH activity influences directly the in vivo flux of hyperpolarised pyruvate through cardiac PDH. The maximum plasma concentration of pyruvate reached during hyperpolarised MRS experiments was approximately 250 µM, equivalent to physiological pyruvate concentrations reached during exercise or with dietary interventions. The concentrations of other metabolites, including lactate, glucose and β-hydroxybutyrate, did not vary during the 60 s following pyruvate infusion. Hence, during the 60-s data acquisition period, metabolism was minimally affected by pyruvate infusion.